ANALISIS POLA RADIASI PEMANCAR ISTA KALISA FM YOGYAKARTA - Priyambodo, Sigit (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2005)
In respect of development of communication system has grown rapidly, there is no problem with the distance, we can know what is happening in the different places even in other country as near as our places. In line with the advance of development of communication devices now days are closed to simple and practical, such as radio, television, cellular phone, and also internet. The radio communication specially, bigger the power transmitted by the antenna, larger area can be covered by the transmitter, that is phenomenon known as the antenna polarization. Radiation pattern analysis of ISTAKALISA FM Yogyakarta transmitter is aimed to recognize the diffuse of transmitting power and the deviation of Istakalisa’s radio antenna. The pattern and deviation can be formed and calculated at first by having tracking and then the data can be obtained where the parameters are able to be utilized for making a pattern and deviation.